Effects of observational learning and goal-focused self-regulation on sport confidence among Chinese speed skating athletes - Fang, L.; Lee, D.; Kwon, S. (International Journal of Sports Science & Coaching, 2026)
This study examined the effects of observational learning and goal-focused self-regulation on sport confidence among Chinese speed skating athletes. An online survey was conducted with 236 speed skaters registered with the Chinese Skating Association participating in the study. Descriptive statistical analysis was used to examine the normality of the data, and correlation analysis was conducted to investigate the relationships among the variables. Furthermore, the mediating effect was examined using structural equation modeling (SEM) with MLR estimator using R Studio, and further verified through bootstrapping procedures. The results indicated that observational learning had a significant indirect effect on sport confidence through goal-focused self-regulation. Moreover, the direct effect of observational learning on sport confidence remained significant even after controlling for goal-focused self-regulation, suggesting a partial mediation effect. These findings underscore the importance of observational learning in speed skating and suggest that both observational learning and goal-focused self-regulation are important factors in enhancing athletes` sport confidence.